The relationship between the intensity of Gasterophilus intestinalis larvae infection and the serum and salivary humoral immune response in horses - Monika Pawlas-Opiela; Paulina Jawor; Józef Galli; Agnieszka Zak-Bochenek; Michał Gorczykowski; Joanna Galli; Zenon Sołtysiak; Tadeusz Stefaniak (Scientific Reports, 2022)
Abstract Infection with Gasterophilus intestinalis (botfly) larvae often occurs in horses. The aim of the study was to isolate the larvae of G. intestinalis and evaluate the serum and salivary humoral immune response using self-developed ELISA in G. intestinalis infected horses. Blood serum or saliva samples were taken from 125 infected horses and 54 uninfected slaughtered horses. The antigens from G. intestinalis larvae were used for development of ELISA in order to evaluate the intensity of G. intestinalis IgG, IgM, and IgA antibody reactivity in the serum or saliva of naturally infected horses and horses without larvae in the gastrointestinal tract (control group). Serum antibodies against second and third larvae’s stadium antigens reacted significantly more intensively in infected than in healthy horses in IgG (p ≤ 0.001; p ≤ 0.05, respectively) and IgA (p ≤ 0.05;p ≤ 0.001, respectively) classes. Salivary IgG and IgA specific’s antibody reactivity was significantly higher in horses with moderate (p ≤ 0.01) and severe infection (p ≤ 0.001) compared to the healthy horses. The determination of the G. intestinalis IgG and IgA antibody activity in saliva and serum may be used for detecting horses moderately and severely infested with larvae.